PERANCANGAN FASILITAS KOMERSIAL AUTO SHOP KOMUNITAS BIMMERS DENGAN PENDEKATAN APLIKASI BRANDING PADA ARSITEKTUR - Stanley Horianto; Gervasius Herry Purwoko (Universitas Ciputra Surabaya, 2023)
Over the past ten years, there have been some instead significant developments in the retail and business sectors. Many companies have realized the importance of application branding in architectural and interior design. By implementing an application approach branding in architectural and interior design can be an important factor that influences company performance and forms trust for a new or old company. Architectural and interior design needs to apply the characteristics of brand a company so that the message the company wants to convey can be seen and attract the public’s attention. Beau Studio exists to provide customers—individuals or companies—with designs that are useful and deemed to further the company’s expansion. Beau Studio will collaborate with German car lovers to create an auto shop specialist in German cars which will also be a gathering place for Bimmers (a community of German car lovers) with an application in the architectural design of buildings. The German car community has developed quite rapidly throughout Indonesia, including Makassar City, a design location city whose business prospects have large potential to develop into progress in the future. Creating a unique workshop will also make Makassar City’s infrastructure appear much more developed and create its uniqueness compared to other workshops.